(untitled) - Prakash, Aseem (Cambridge, 2000)
Over the past two decades environmental issues have become important in public and business policy. This book asks why firms sometimes voluntarily adopt environmental policies that go beyond legal requirements. Prakash argues that existing explanations, especially from neoclassical economics, concentrate on external factors at the expense of internal dynamics. His argument is supported by analysis of two firms, Baxter International Inc. and Eli Lilly and Company, including interviews with managers, and access to meetings and documents. The book will be of interest to students of business and environmental studies, as well as political economy and public policy.
Keywords: Quản lý công nghiệp,Environmental policy,Industrial management,International business enterprises,Chính sách môi trường; Khía cạnh môi trường,Environmental aspects,Environmental aspects